Biochemical markers in the diagnosis of chondral defects following anterior cruciate ligament insufficiency - Streich, Nikolaus; Zimmermann, David; Schmitt, Holger; Bode, Gerrit (International orthopaedics, 2011)
Purpose: The aim of this study was to determine the value of systemic biochemical markers of bone turnover—urine levels of cross-linked C-terminal telopeptide I (uCTX-I), urinary C-terminal telopeptide II (uCTX-II) and serum cartilage oligomeric matrix protein (sCOMP)—in the diagnosis of chondral defects after anterior cruciate ligament (ACL) rupture. Thirty-eight patients with previous ACL rupture were included. Methods: Magnetic resonance imaging (MRI) of the injured and the intact knee joint was performed with volumetric measurement of volume and area of cartilage (VC/AC), area of subchondral bone (cAB), and area of subchondral bone denuded and eroded (dAB). Biochemical markers were measured using commercially available enzyme-linked immunoassays. Results: MRI-based volumetric cartilage measurement showed significant differences between the injured and the intact knees. uCTX-I, sCOMP and in parts uCTX-II correlated well with MRI parameters. CTX-I showed a significant correlation with VC and AC of the whole knee joint. Conclusions: The results suggest that uCTX-I, uCTX-II and sCOMP could identify patients with focal cartilage lesions from an early stage of osteoarthritis of the knee.
Gesehen am 24.10.2022